LEARNING PHYSICS USING POLOPALO ON SOUND WAVES - Ujulu, Afandi
Designing learning is important to help students in the learning process. This study aims to make a Physics learning design for sound wave material using the Polopalo, which is a traditional musical instrument of Gorontalo province, by first analyzing its physical properties. The method used is experimental research, by analyzing of the physical properties of Polopalo and designing learning sound waves using Polopalo. The design refers to an independent curriculum that is implemented through Inquiry-Based Learning (IBL) involving experimental activities. The results showed that the density value of Polopalo bamboo was obtained in the range of 0.58 – 0.90 g/cm3 . This value is quite high but within the range studied by other researchers. Furthermore, the length of the air column in the Polopalo was not in accordance with the experimental and theoretical results of the air column. This shows that the size of the Polopalo resonant tube does not match the frequency, so the resonance might occur imperfectly. For the prediction of the modulus of elasticity of Polopalo bamboo, within the range is 29.13 – 58.36 GPa. The slight difference in the geometry of the Polopalo and the tuning fork cause the value is quite high. The learning design containing sound wave experiments using Polopalo can only be used when observing resonance because the sound not continuously produced. Therefore, an online tone generator is used as a sound source to carry out experiments on beat, reflection, and interference of sound waves